STRATEGI PENINGKATAN IN PUT DAN MUTU LULUSAN FAKULTAS DAKWAH DAN ILMU KOMUNIKASI UIN MATARAM - Ahyar Ahyar (Universitas Islam Negeri (UIN) Mataram, 2018)
Improving the quality of inputs and graduates of Higher Education is a basic program based on the program through an integrated approach starting from input-process, the output out to come out. The PMI Department is one of the majors at FDIK, Mataram UIN which continues to improve even though since its opening in 2007 until 2017 from the inside side it still experiences a less encouraging trend. Therefore, through this research, we want to find the image of the community towards its existence, the direction of the policy and the strategy of increasing the graduates' input. This study uses survey research, where researchers try to find people's perceptions through closed questions. The method of collecting data through questionnaires, and coupled with interviews, observation and documentation. While data analysis uses an interactive model analysis through data collection, data reduction and verification or conclusion. The credibility of data is through an extension of the time of research and triangulation. The results of the study found that a) the perception or image of the community about the existence of the FDI PMI Department Mataram UIN is still formalist and normative meaning that it only sees things that are not substantive, b) Policy directions through two models, namely the direction of academic and sociological policies, and c ) improvement strategies through internal academic reinforcement and external reinforcement (partnership).